Analisis Potensi Energi Listrik dari Biogas Campuran Sampah Daun Ketapang dan Tinja Kerbau - Falmansyah, Muhammad Ridho; Jelita, Marhama (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2024)
Leaf and twig waste accounts for 12.99% of Indonesia’s waste problems. One of the fertile plants that can produce 10 kg of leaf waste per day for an area of 1200 m3 is the ketapang tree. The ketapang tree has leaf waste that has the potential to become biogas through the fermentation process but produces a small amount of biogas, so the increase is done by mixing buffalo feces. Fermentation of a mixture of ketapang leaf waste and buffalo feces using a Batch-type digester by comparing using starter and non-starter to produce potential biogas and electrical energy. In the fermentation process of the mixture of ketapang leaf waste and buffalo feces, the temperature of the non-starter digester ranges from 26.3-32.6 °C and the starter 26.3-33 °C, the pH of the non-starter digester is in the range of 6.4-6.9 while the starter is 5.8-6.6. Biogas production generated from a mixture of ketapang leaf waste and buffalo work feces for non-starter is 0.00465 m3 and starter 0.0028 m3 with potential electrical energy generated non-starter 0.022 kWh and starter 0.013 kWh. Biogas and electrical energy production from a mixture of ketapang leaf waste and buffalo feces with non-starter is higher than using a starter.Keywords - Biogas, Ketapang Leaf Waste, Buffalo Feces, Starter, Electrical Energy.